Solar energy utilization in desalination power plan - Erdiansyah; Kristyadi Tarsisius; Diki Ismail Permana (JTTM : Jurnal Terapan Teknik Mesin, 2023)
A steam power plant (PLTU) uses demin water to generate 3x350 MW of electrical energy. Reverse Osmosis Desalination system is used to treat the 190 m3/hour of desalinated water that is produced from seawater. Solar energy will replace the 225.41 kW of electrical energy required for the RO desalination pump in order to lessen pollution and the greenhouse effect caused by PLTU. The PLTU is situated in Pelabuhan Ratu Sukabumi, West Java. This region has a solar radiation potential of 3.189 kWp/day/m2 and a deployment space for PV modules of 6,167 m2, divided into two zones: the ground and the roof. The needs analysis is carried out by utilizing software simulations that estimate the power requirements of desalination pumps and the potential of electrical energy from solar radiation based on land availability. According to the modeling findings, PLTS can produce 1024 MWh/year of electrical energy with 1,458 pieces of 450 Wp PV modules and 5 units of 120 kW inverters.